Reconstruction of the 1945 Constitution for strengthening the legal framework of Indonesia Environmental Law: Rekonstruksi UUD 1945 Menuju Penguatan Hukum Lingkungan Indonesia - Susanto, Antono Adhi (Constitutional Court of the Republic of Indonesia, Indonesia, 2024)
The Anthropocene era was marked by a decline in the quality of the environment including being influenced by the law itself, for example the Job Creation Law was considered to have a negative impact on efforts to protect the environment. This research will analyze the development of legal instruments and the role of the Constitutional Court in environmental protection. This research will be conducted by studying legal literature. The urgency of changing the environmental law political paradigm (green policy) in Indonesia based on the ecocentrism paradigm will provide stronger environmental law political guidelines. Efforts to strengthen the paradigm of environmental protection are carried out by reconstructing the 1945 Constitution of the Republic of Indonesia by granting rights to the environment and setting state obligations. There is a role for the Constitutional Court through Decision Number 32/PUU-VII/2010 and Number 18/PUU-XII/2014 by providing guidelines for the development of more comprehensive environmental law.